The Migration of Data and Other Life Forms: A Sound Installation for the 70th Anniversary of the Darmstadt Summer Courses. - VARCHAUSKY, NICOLÁS (Leonardo Music Journal, 2018)
The article discusses a sound installation premiered during the 70th anniversary of the New Music Summer Courses in Darmstadt. The project proposes a dialogue between the archive of the Internationales Musikinstitut Darmstadt (IMD), which preserves the voices of contemporary music composers who lectured at the summer courses, and Archivo PAIS, the author's personal archive of anonymous voices of street vendors, informal preachers, institutional announcers and street artists. Speech analysis software, transducers, modified stethoscopes and a 15-meter-long by 4-meter-high fence were used to reflect on issues of survival, access and displacement though sound.